2013
DOI: 10.1007/s12663-013-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cephalometric Study of the Pharyngeal Airway Space in Patients Submitted to Orthognathic Surgery

Abstract: Introduction Pharynx is a muscular organ with is sustained by craniofacial bones. It is divided into nasal, oral and hipopharynx, and can be considered as a tube that serves both respiratory and digestive systems. Its anatomical morphology permits that factors facilitate its obstruction, leading to the sleep apnea syndrome. One of the treatment consists of surgical mandibular advancement, increasing pharyngeal dimensions. The aim of this study was evaluate the cephalometric changes in the pharyngeal airway spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
15
0
10
Order By: Relevance
“…7,9 Changes in the development of the maxilla and mandible (due to developmental deformities, orthognathic surgery, and orthodontic treatment), may cause a predisposition for changes in the volume of the pharynx, which are also accompanied by changes in the positioning of the hyoid. 2,10 The main areas of change are the soft palate (nasopharynx), the lateral walls of the pharynx (oropharynx), and the base of the tongue (hypopharynx), thus emphasizing the importance of evaluating the different pharyngeal subregions. 2 The present study found that the hyoid bone position was more highly correlated to measures of the oropharynx and hypopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,9 Changes in the development of the maxilla and mandible (due to developmental deformities, orthognathic surgery, and orthodontic treatment), may cause a predisposition for changes in the volume of the pharynx, which are also accompanied by changes in the positioning of the hyoid. 2,10 The main areas of change are the soft palate (nasopharynx), the lateral walls of the pharynx (oropharynx), and the base of the tongue (hypopharynx), thus emphasizing the importance of evaluating the different pharyngeal subregions. 2 The present study found that the hyoid bone position was more highly correlated to measures of the oropharynx and hypopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 The main areas of change are the soft palate (nasopharynx), the lateral walls of the pharynx (oropharynx), and the base of the tongue (hypopharynx), thus emphasizing the importance of evaluating the different pharyngeal subregions. 2 The present study found that the hyoid bone position was more highly correlated to measures of the oropharynx and hypopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations